A FUZZY AHP AND ELECTRE METHOD FOR SELECTING STABILIZING DEVICE IN SHIP INDUSTRY - Demirel, Hakan; Balin, Abit; Celik, Erkan; Alarcin, Fuat (UNIV ZAGREB FAC MECHANICAL ENGINEERING & NAVAL ARCHITECTURE, 2018)
Roll stabilizer systems are studied for different types of ships by many researchers. It is well known that roll motion is caused by external disturbances (wave, wind etc) and large roll motion can cause capsizing easily. In addition, undesirable roll motion effect badly crew performance and passenger comfort. So, roll reduction has an important role for all types of ships. In our study, we proposed a fuzzy AHP (Analytic Hierarchy Process) and ELECTRE (Elemination and Choice Translating Reality English) method for selecting the most effective roll stabilizing system for a trawler type fishing vessel. Alternatives and criteria in relation to the stabilizers are determined by experts' experiences and literature review. This paper intends to give a comprehensive procedure for determining the most suitable roll motion stabilizing system of trawler for safety and efficiency fishing in the open literature.
Keywords: AHP; ELECTRE; fuzzy sets; roll stabilizing system; trawler; RUDDER ROLL STABILIZATION; VIKOR; IDENTIFICATION; EXTENSION; SYSTEM; BOARD; Engineering